(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The aim of this study is to identify effective methods for improving students’ knowledge through the use of information technologies in teaching biology based on interdisciplinary connections. The research involved experiments to assess students’ knowledge, interdisciplinary integration, and the application of information technologies. The results indicate that combining interdisciplinary connections with information technologies significantly enhances students’ learning outcomes. The findings of this study can serve as a basis for effectively organizing biology lessons and applying modern technologies in the educational process.